2005
DOI: 10.1063/1.2149156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cl2∕Ar dry etching on p-GaN with Ni∕Au metallization characterization

Abstract: This work investigates the effect of Cl 2 / Ar dry etching on p-GaN. The root-mean-square ͑rms͒ surface roughness is measured, and the depth display ͑Bearing analysis͒ is monitored. The current-voltage characteristics of etched p-GaN with Ni ͑20 nm͒ /Au ͑20 nm͒ metallization are studied. Experimental results indicate that the etching rate does not increase significantly with the Cl 2 flow rate at a constant power or chamber pressure. The Bearing ratio data exhibit a much stronger variation with etch conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Additionally, ZnO film with pure H 2 dry etching treatment shows high rms roughness due to only physical H 2 bombardment without the chemical reaction from CH 4 gas. The corresponding AFM measurements at various rf power reveal that nanorods were present on the surface of all n-ZnO samples after dry etching, as observed in other materials [11][12][13]. The inset in Fig.…”
Section: H 2 and Ch 4 Flow Ratesmentioning
confidence: 68%
“…Additionally, ZnO film with pure H 2 dry etching treatment shows high rms roughness due to only physical H 2 bombardment without the chemical reaction from CH 4 gas. The corresponding AFM measurements at various rf power reveal that nanorods were present on the surface of all n-ZnO samples after dry etching, as observed in other materials [11][12][13]. The inset in Fig.…”
Section: H 2 and Ch 4 Flow Ratesmentioning
confidence: 68%
“…The authors have elsewhere applied the bearing ratio to analyze the surface property of nanorods. 21 Bearing analysis reveals the percentage of the surface ͑the "bearing ratio"͒ that lies above or below a given height. This measurement provides additional information beyond standard roughness measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding AFM measurements at various Cl 2 / Ar gas flow rates reveal that nanorods were present on the surfaces of all ZnO samples following dry etching, as observed on other materials. [19][20][21] Figures 3͑b͒-3͑e͒ display nanorods obtained at an Ar flow rate of 10 SCCM, a working pressure of 60 mTorr, and a rf power of 300 W with various Cl 2 flow rates. Jeong et al 22 reported that x-ray photoelectron spectroscopy spectra indicate the formation of ZnCl 2 on the etched surface after the dry etching process with Ch 4 / H 2 / Ar/ Cl 2 gas mixture.…”
Section: Resultsmentioning
confidence: 99%
“…16,17) Obviously, the electrical properties of p-type GaN are strongly dependent on plasma etching. 18,19) Therefore, the current blocking region or selective high barrier region (SHBR) below the p-pad electrode can be easily implemented by ICP etching on p-type GaN. Additionally, ICP etching provides a more flexible and effective blocking pattern to modify the injection current distribution on p-type GaN without any additional processes, such as a Ni catalytic process 20,21) or the deposition of SiO 2 as a blocking layer.…”
Section: Introductionmentioning
confidence: 99%